Anatomical Characteristics of some Woody Plants of the Angmagssalik District of Southeast Greenland. - Miller, Howard J. (Meddelelser om Grønland, 1975)
Ten species are represented by the 40 wood specimens collected in 1969 from the Angmagssalik District of S.E. Greenland. Information concerning collection localities, diameter of wood specimens, number and breadth of growth rings and eccentricity is given. A comparison of growth ring observations is made with those made by KRUUSE (1912), in three species from the same area, in relation to their growth form and environment. An anatomical description of the wood of the 10 species has been made together with an evaluation of some of the anatomical characteristics. Trends towards a modification of the wood due to environmental factors are indicated, but the fact that caution must be exercised when carrying out such an investigation is stressed, with special emphasis on the need for more accurate information regarding environment, the size and age of specimens.